Classroom Allocation System with User Experience Design - Chompoonuch Jinjakam; Pichamol Phothong; Piyarat Pearodwong; Thana Hongsuwan (My University, 2021)
Classroom allocation is one of the most important problems of academic management. The new semester may vary on different sizes of the student population, the number of subjects, provided classrooms, and so forth. Over-allocation and under-allocation of the classroom space directly affect the feeling comfortably of students. Furthermore, not only the facilities provided inside the classroom but also the classroom distance affect the quality of teaching and learning of room members. This paper studies classroom allocation in the School of Engineering, King Mongkut's Institute of Technology, Ladkrabang, Thailand. The main cohort is around 11,310 Thai bachelor students that are studying in 55 Thai courses. These courses have 1,624 subjects. Some departments provide room for their courses, but the main course of the first year and second-year students are managed under the central classroom allocation. Total 128 central classrooms provided in 5 buildings (data on 8 September 2020), which vary on size and number of seats. From traditional manual management to web-based management, user experience design is chosen method to improve the satisfaction of the automatic system. User interviews are applied with the 30s-years experienced staffs in the academic department and physical and environment department in the School of Engineering, KMITL. Cases of lecturers' scenarios are transferred to the function of the classroom allocation system. Classroom allocation in functions of capacity and location management is proposed in a user- friendly web-based program. Automatic classroom allocation results 203 of 245 subjects use central classroom location similar to the traditional manual arrangement, and 26 subjects are set in the different building from the assigned zone that improve from the traditional management.
Keywords: Educational Environments and Student Outcomes; Scheduling and Timetabling Solutions